Unusual Shipments in Air Transport - Štrumberger, Nada (Promet - Traffic&Transportation)
The article lists the unusual shipments in air transport.Over 2% of the annual cargo air transportation are the unusualshipments. Good co-ordination of the reception and deliveryprocesses of unusual shipments is one of the importantfactors in providing good and fast service knowing the basicregulations in air traffic.